2001
DOI: 10.1161/hq1001.097021
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Smoking Causes Nitroglycerin Resistance in Platelets by Depletion of Intraplatelet Glutathione

Abstract: Abstract-We investigated whether platelet responsiveness to nitroglycerin (NTG) is maintained in long-term smokers and if not, the mechanism. In the absence or presence of NTG, intraplatelet reduced glutathione (GSH) levels and ADP-induced platelet aggregation and intraplatelet cGMP levels were measured in 10 long-term smokers and 10 age-matched nonsmokers. The intraplatelet GSH level was significantly lower in smokers than in nonsmokers (PϽ0.05).Platelet aggregation was dose-dependently inhibited by NTG in bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0
2

Year Published

2002
2002
2021
2021

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 35 publications
0
18
0
2
Order By: Relevance
“…3,18 Indeed, we have previously shown that impaired PDNO bioactivity and augmented platelet aggregability in smokers may be caused by an imbalance of the intraplatelet redox state through increased oxidative stress. 14,19 In general, EDNO and PDNO act in coordination as anti-atherothrombogenic molecules, 3,4,8,9 and in the previous clinical studies, impaired EDNO or PDNO has been associated with an increase in cardiovascular events such as acute coronary syndromes. 20,21 Accordingly, impaired EDNO and PDNO bioactivities may synergistically contribute to atherothrombogenesis in patients with coronary risk factors.…”
Section: Discussionmentioning
confidence: 99%
“…3,18 Indeed, we have previously shown that impaired PDNO bioactivity and augmented platelet aggregability in smokers may be caused by an imbalance of the intraplatelet redox state through increased oxidative stress. 14,19 In general, EDNO and PDNO act in coordination as anti-atherothrombogenic molecules, 3,4,8,9 and in the previous clinical studies, impaired EDNO or PDNO has been associated with an increase in cardiovascular events such as acute coronary syndromes. 20,21 Accordingly, impaired EDNO and PDNO bioactivities may synergistically contribute to atherothrombogenesis in patients with coronary risk factors.…”
Section: Discussionmentioning
confidence: 99%
“…Muscat et al 2004 109 Haramaki et al 2001 110 Takajo et al 2001 111 Diabetes Enhanced platelet O 2 Ϫ production in diabetic subjects is associated with enhanced platelet activation. Reduction of platelet activation in diabetic subjects by antioxidant vitamins.…”
Section: Cardiovascular Risk Factors and Diseases Associated With Enhmentioning
confidence: 99%
“…We have previously shown that long-term smoking impairs platelet-derived nitric oxide (PDNO) release (6), which acts as a negative feedback mechanism to inhibit not only platelet aggregation (11) but also recruitment after aggregation (12). Furthermore, we have recently shown that impaired PDNO bioactivity and augmented platelet aggregability in long-term smokers are related to the imbalance of the intraplatelet redox state, suggesting the smokinginduced oxidative stress for platelet activation (5,6). Thus, smoking-induced platelet-mediated thrombotic mechanisms may be involved in the pathophysiology of coronary artery disease of long-term smokers.…”
mentioning
confidence: 99%